SINTESIS DAN ANALISIS KANDUNGAN MINERAL DAN KARAKTERISTIK SIFAT LISTRIK NANOPARTIKEL PASIR BESI PANTAI TELINDUNG KABUPATEN LOMBOK TIMUR - Asri, Laelatul; Didik, Lalu A.; Bahtiar, Bahtiar (Universitas Pendidikan Ganesha, 2021)
This study aims to determine the mineral content as well as the characteristics of the electrical properties of the iron sand nanoparticle samples of the Telindung beach. Synthesis of iron sand nanoparticles can be done by sharing one method, namely the coprecipitation method. In the coprecipitation process, researchers used HCl and NH4OH solutions to make a sample of nano-sized iron sand (nanoparticles) of 5 samples with different sampling distances of 3 meters, 6 meters, 9 meters, 12 meters, and 5 meters. Each finished sample is then analyzed for its mineral content using AAS. The results shows that the higher the sampling distance, the higher the mineral content, namely the total Fe in the sample of iron sand nanoparticles (8.28%, 8.79%, 8.85%, 9.07% and 9.74%). Characteristics of electrical properties namely resistivity using 4 point probes with a series of power supply devices and multimeters by making 1 sample 5 times the measurement so that the value of resistivity (8.3 x 104 ,m, 9.1 x 104 Î©m, 9.6 x 104 Î©m, 10 Î©m, 3 x 104 Î©m, 11.3 x 104 Î©m), for dielectricity using a plate parallel to the LCR meter, one sample of 10 times the measurement so as to obtain the value of the dielectric constant (6.4 x 104 F, 7.9 x 104 F, 9 , 8 x 104 F, 11.6 x 104 F and 13.1 x 104). So it can be said that the higher the value of minerl candlengan that is the total Fe, the higher the value of the characteristic electrical properties are resistivity and dielectricity.